2020
DOI: 10.1016/j.apsb.2020.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Berberine diminishes cancer cell PD-L1 expression and facilitates antitumor immunity via inhibiting the deubiquitination activity of CSN5

Abstract: Programmed cell death-1 (PD-1)/programmed cell death ligand-1 (PD-L1) blocking therapy has become a major pillar of cancer immunotherapy. Compared with antibodies targeting, small-molecule checkpoint inhibitors which have favorable pharmacokinetics are urgently needed. Here we identified berberine (BBR), a proven anti-inflammation drug, as a negative regulator of PD-L1 from a set of traditional Chinese medicine (TCM) chemical monomers. BBR enhanced the sensitivity of tumour cells to co-cultured T-cells by decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
117
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(118 citation statements)
references
References 48 publications
1
117
0
Order By: Relevance
“…Patients with expression of PD-L1 on either cancer cells or on TILs prefer to respond to anti-PD-1/PD-L1 therapy 17 , 18 , 19 . Meanwhile, the expression of PD-L1 can be regulated by many factors 20 , 21 . Hence, it is critical to comprehend the pathways regulating expression and stability of PD-L1.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with expression of PD-L1 on either cancer cells or on TILs prefer to respond to anti-PD-1/PD-L1 therapy 17 , 18 , 19 . Meanwhile, the expression of PD-L1 can be regulated by many factors 20 , 21 . Hence, it is critical to comprehend the pathways regulating expression and stability of PD-L1.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that therapeutic modulating of ion channels using phytochemical compounds in lung cancer could be a future endeavor because modulating hyperpolarization to resting membrane potential can effectively restore CSCs to their quiescence [ 178 ]. Recent mounting evidence has shown that phytochemical compounds have the potential to be used as an alternative to immune checkpoint inhibitors against Programmed cell death 1 ligand 1 (PDL1) such as the cases of EGCG and berberine [ 179 , 180 ]. Future study is still necessary to demonstrate whether the utilization of phytochemical compounds can help alleviate the resistance challenge and side effects of immunotherapy.…”
Section: Discussion and Future Perspectivementioning
confidence: 99%
“…Baicalin participates in the regulation of TLRs signaling pathways to exert immunomodulatory effects, thereby inhibiting the migration of cancer cells [ 36 ]. Berberine can inhibit the expression of PD-L1 in tumor cells and activate T cells to participate in tumor immune regulation [ 37 , 38 ]. It was found that CXCL12 and CCL27 played an important role in CM metastasis, and were mainly involved in SKMC metastasis through the CXCR4-CXCR7-CXCL12 axis and CCL27-CCR10 axis [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%